2020
DOI: 10.4018/978-1-7998-1029-2.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Leadership and Change in Higher Education

Abstract: Higher educational institutions are widening participation through the introduction of new programs, using different approaches to deliver learning so that many people can have access to education. With the growing number of students in our higher educational institutions, coupled with learners who are working and by virtue of their job commitments cannot do traditional face-to-face education, using information technology (IT) to support lessons in higher education institutions has become very laudable. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…70 The common belief that disability is punishment from God results in the practice of hiding children with disabilities in the house so that their supposed sins do not become known. 71 Her research team found children with disabilities who were kept hidden away for their whole lives. A women living with albinism in Malawi mentioned, in an interview with Amnesty International, that she and her sister -who also lives with albinism -were given food separately from the other children.…”
Section: The Invisibility and Exclusion Discoursementioning
confidence: 99%
“…70 The common belief that disability is punishment from God results in the practice of hiding children with disabilities in the house so that their supposed sins do not become known. 71 Her research team found children with disabilities who were kept hidden away for their whole lives. A women living with albinism in Malawi mentioned, in an interview with Amnesty International, that she and her sister -who also lives with albinism -were given food separately from the other children.…”
Section: The Invisibility and Exclusion Discoursementioning
confidence: 99%